Physical activity as one of the elements of healthy behavior. Comparative analysis of 11-, 12- and 13-year-old students in selected schools in Poland and Norway - Kilanowska, Jolanta; Muszkieta, Radosław (Pedagogy and Psychology of Sport, 2019)
Some communities have valued and still value contact with nature and an active lifestyle in its bosom than others. It is worth using the experience of such societies. Norway is definitely a country where such activity has been and is being cultivated in a very effective and common way. The aim of the study was to determine selected aspects of physical activity of students aged 11-13 from Poland and Norway.